2008
DOI: 10.1111/j.1600-0420.2007.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Success rates for switching to dorzolamide/timolol fixed combination in timolol responders who are insufficiently controlled by latanoprost monotherapy

Abstract: ABSTRACT.Purpose: We aimed to investigate the safety and efficacy of dorzolamide ⁄ timolol fixed combination (DTFC) in timolol responders with ocular hypertension or open-angle glaucoma who switched to DTFC because of insufficient control on latanoprost. Methods:We carried out a prospective, open-label cohort study with an active-historical control in which qualifying patients must have been treated with latanoprost monotherapy for at least 4 weeks, must have demonstrated insufficiently controlled intraocular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 13 publications
2
6
0
1
Order By: Relevance
“…Mizoguchi et al reported that the IOP was reduced from 15.6±2.0 mmHg at baseline to 13.7±2.2 mmHg at 8 weeks after adding DTFC to PGA monotherapy (n=40), and the percentage reduction of IOP from baseline was 11.7%±13.1% at 8 weeks 15. In our study, prior medications were switched to DTFC, whereas DTFC was added to latanoprost by Mizoguchi et al but the IOP reduction rate obtained in the present study was similar to those reported previously 14,15. Considering these results, an IOP reduction rate of 11.7% after switching to DTFC may be sufficient for protection against visual field progression.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mizoguchi et al reported that the IOP was reduced from 15.6±2.0 mmHg at baseline to 13.7±2.2 mmHg at 8 weeks after adding DTFC to PGA monotherapy (n=40), and the percentage reduction of IOP from baseline was 11.7%±13.1% at 8 weeks 15. In our study, prior medications were switched to DTFC, whereas DTFC was added to latanoprost by Mizoguchi et al but the IOP reduction rate obtained in the present study was similar to those reported previously 14,15. Considering these results, an IOP reduction rate of 11.7% after switching to DTFC may be sufficient for protection against visual field progression.…”
Section: Discussionsupporting
confidence: 89%
“…The IOP reduction rate from the baseline was 11.4%±14.4% at 36 months after switching (Table 2). Sonty et al reported that the IOP was reduced from 21.4±2.5 mmHg at baseline to 17.9±3.5 mmHg at 12 weeks after switching to DTFC from latanoprost (n=57) 14. Mizoguchi et al reported that the IOP was reduced from 15.6±2.0 mmHg at baseline to 13.7±2.2 mmHg at 8 weeks after adding DTFC to PGA monotherapy (n=40), and the percentage reduction of IOP from baseline was 11.7%±13.1% at 8 weeks 15.…”
Section: Discussionmentioning
confidence: 99%
“…The percent reduction of IOP from the baseline value was 11.7%±13.1% at 8 weeks 13. The percent reduction of IOP in the present study was similar to those reported previously 12,13. However, there is not necessarily agreement as to whether DTFC would reduce the IOP after switching.…”
Section: Discussionsupporting
confidence: 88%
“…The percent reduction of IOP from baseline was 14.5%±14.2% and 12.8%±15.2% at 6 and 36 months after switching, respectively (Figure 2A). Sonty et al reported that DTFC reduced the IOP from 21.4±2.5 mmHg at baseline to 17.9±3.5 at 12 weeks after switching from latanoprost (n=57) 12. Mizoguchi et al reported that DTFC reduced the IOP from 15.6±2.0 mmHg at baseline to 13.7±2.2 mmHg at 8 weeks after addition to PGA monotherapy (n=40).…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan çalışmalarda, monoterapiden geçişte her iki ajan ile tatminkar seviyelerde ilave GİB düşüşleri bildirilse de, bu iki sabit bileşimin 24 saatlik GİB kontrolünde etkileri ve birbirine üstünlükleri henüz tam açık değildir. [9][10][11][12] Shin ve ark. 13 Çalışmaya alınan hastaların ayrıntılı öyküleri alındı ve Snellen eşeli ile en iyi düzeltilmiş görme keskinlikleri saptandı.…”
Section: Gi Riflunclassified